Variety changing of winter soft wheat as a method to improve productivity and resistance to abiotic environmental factors - V. L. Gaze; E. V. Ionova; D. M. Marchenko; V. A. Likhovidova (Зерновое хозяйство России, 2019)
The article deals with the use of variety changing to increase productivity and resistance of winter wheat varieties to abiotic environmental factors. As a result of the variety changing and sequence of varieties successively replacing each other, the productivity increased from 3.3 t/ha (stage I) to 6.2 t/ha (stage VII). It has been established that the varieties belonging to the steppe ecotype possess a higher level of drought resistance in comparison with the varieties of the forest-steppe ecotype. According to the stages of variety changing drought tolerance ranged from 69–70% (stage I) to 95–99% (stage VII). The level of heat resistance from I to V stage of the variety changing was low (48–70%), excluding the variety “Rostovskaya” (III stage of variety changing) with its heat resistance of 81%. The varieties of the sixth and seventh stage of the variety changing possess high heat resistance (90–99%). The replacement of the cultivated varieties with new, more adaptive and highly productive ones will allow stabilizing grain production and rising its quantity.